Validity of instruments for assessment of scientific literacy and critical thinking of students based on multiple intelligence in acid-base material - Muji Rahayu Wigati; Asmadi M. Noer; Lenny Anwar (Jurnal Pendidikan Kimia (JPKIM), 2023)
This research aims to create an assessment tool to evaluate students' scientific reading comprehension and critical thinking ability based on multiple intelligences on acid-base materials and to determine the validity of this study rating tool. The research methodology uses the Borg and Gal research and development model. This research phase continues into the development phase. The assessment instrument developed in this study consists of sixteen items of description test questions that refer to science literacy indicators consisting of four indicators are science as a body of knowledge; science as a way of investigation; science as a way of thinking; and the interaction of science, technology and society. Then the assessment instrument refers to critical thinking which consists of five indicators: providing a simple explanation, building basic skills, inference, providing further explanation, and developing strategies and tactics. This assessment instrument is based on multiple intelligences consisting of five types of intelligence: logical-mathematical, verbal-linguistic, visual-spatial, rhythmic-musical, and naturalistic. The validation of this assessment instrument is carried out by five validators. Validation by material experts is measured using the Guttman scale. Validity according to experts, namely aspects of material, language, and construction, obtained on average expert validation ranges from 90,33 – 94,7% and 16 questions are declared valid. Assessment instruments have been developed to be useful as a measure of a student's creative thinking ability.Keywords: Acid-base; Critical thinking; Instrument for assessment; Multiple intelligences; Science literacy